2022
DOI: 10.3389/fonc.2022.848395
|View full text |Cite
|
Sign up to set email alerts
|

Up-Regulation of TRIM32 Associated With the Poor Prognosis of Acute Myeloid Leukemia by Integrated Bioinformatics Analysis With External Validation

Abstract: BackgroundAcute myeloid leukemia (AML) is a malignant and molecularly heterogeneous disease. It is essential to clarify the molecular mechanisms of AML and develop targeted treatment strategies to improve patient prognosis.MethodsAML mRNA expression data and survival status were extracted from TCGA and GEO databases (GSE37642, GSE76009, GSE16432, GSE12417, GSE71014). Weighted gene co-expression network analysis (WGCNA) and differential gene expression analysis were performed. Functional enrichment analysis and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 44 publications
(45 reference statements)
0
2
0
Order By: Relevance
“…Yu et al 33 recently used WGCNA to show that high expression of LOC541471, GDAP1, SOD1 and STK25 is associated with poor survival of patients with AML. Xu et al 34 GATA1) and pathways in AML using WGCNA. In the present study, we identified six hub genes related to survival of patients with AML by applying WGCNA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Yu et al 33 recently used WGCNA to show that high expression of LOC541471, GDAP1, SOD1 and STK25 is associated with poor survival of patients with AML. Xu et al 34 GATA1) and pathways in AML using WGCNA. In the present study, we identified six hub genes related to survival of patients with AML by applying WGCNA.…”
Section: Discussionmentioning
confidence: 99%
“…recently used WGCNA to show that high expression of LOC541471 , GDAP1 , SOD1 and STK25 is associated with poor survival of patients with AML. Xu et al 34 . also used WGCNA to show that TRIM32 is associated with a poor prognosis in patients with AML.…”
Section: Discussionmentioning
confidence: 99%